1974
DOI: 10.1128/jb.117.2.329-336.1974
|View full text |Cite
|
Sign up to set email alerts
|

Control of Deoxyribonucleic Acid Synthesis in a Bacillus subtilis Mutant Temperature Sensitive for Initiation of Chromosome Replication

Abstract: We used a Bacillus subtilis mutant described previously, which is temperature sensitive for initiation of replication. The inhibition of deoxyribonucleic acid synthesis occurring at 45 C was shown to be reversed when the temperature is lowered even in the absence of protein synthesis. If the bacteria are returned to 30 C, after a prior period at 45 C, they are able to initiate the first round of replication in the presence of chloramphenicol, but the initiation of the second round still requires protein synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1975
1975
1991
1991

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Furthermore, the cells retain complete viability during the period for which they were at 45 C. As in the case of B. subtilis 168 ts 37, an initiation mutant isolated by Laurent and Vannier (7)(8)(9), dna-20(Ts) has been found particularly useful in preliminary studies on possible transcriptional and translational events associated with the initiation of chromosome replication (P. Upcroft, H. J. Dyson, and R. G. Wake, Proc. Aust.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the cells retain complete viability during the period for which they were at 45 C. As in the case of B. subtilis 168 ts 37, an initiation mutant isolated by Laurent and Vannier (7)(8)(9), dna-20(Ts) has been found particularly useful in preliminary studies on possible transcriptional and translational events associated with the initiation of chromosome replication (P. Upcroft, H. J. Dyson, and R. G. Wake, Proc. Aust.…”
Section: Discussionmentioning
confidence: 99%
“…Initiation of the first cycle requires RNA synthesis but not protein synthesis (17). Depending on the length of the preceding period at a nonpermissive temperature, the initiation of the second cycle becomes chloramphenicol resistant and rifampin resistant during the first cycle, well before the second cycle itself begins (18). This paper shows that, after purification and complete denaturation of DNA, an in vivo-labeled RNA is found associated with high-molecular-weight DNA.…”
mentioning
confidence: 81%
“…wave showed a maximum between 30 and 40 min, i.e., during the elongation of the first replication cycle and thus before the initiation of the second cycle. In an earlier study (18), it was shown that, after a period at 45C, the initiation of the second cycle became chloramphenicol resistant and rifampin resistant before the initia-tion itself began. (iii) We have not yet studied the time of appearance of the initiation potential for the third replication cycle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation